A Drift-Free Left Invariant Control System on the Lie Group SO(3)×R3×R3. (31st March 2015) - Pop, Camelia
Abstract : A controllable drift-free system on the Lie groupG = S O ( 3 ) × R 3 × R 3 is considered. The dynamics and geometrical properties of the corresponding reduced Hamilton's equations ong ∗, ·, · - are studied, where·, · - is the minus Lie-Poisson structure on the dual spaceg ∗ of the Lie algebrag = s o ( 3 ) × R 3 × R 3 ofG . The numerical integration of this system is also discussed.